Digitalization of Ethno Constructivism Based Module for Elementary School Students - Asrial, Asrial; Syahrial, Syahrial; Kurniawan, Dwi Agus; Anandari, Qalbi Shanaz (Universitas Negeri Malang, 2019)
This research develops e-module teaching materials by using a digitalized book application based on ethno constructivism and also discerns students' responses to the e-modules. We employed the ADDIE model (Analysis, Design, Develop, Implement, and Evaluate) to create the books. The ADDIE model consists of five steps, namely (1) introduction, (2) planning, (3) development, (4) implementation, and (5) evaluation. The subjects of this study were 21 fifth-grade students of elementary schools 112/I. The results of this study captured that the product was favored by most of the students with percentages of interest (72.73percent), motivation (77.27percent), and perception (63.6percent).